2013
DOI: 10.1016/j.amepre.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

The Ask–Advise–Connect Approach for Smokers in a Safety Net Healthcare System

Abstract: Background Since smoking has a profound impact on socioeconomic disparities in illness and death, it is crucial that vulnerable populations of smokers be targeted with treatment. The US Public Health Service recommends that all patients be asked about their smoking at every visit, and that smokers be given brief advice to quit and referred to treatment. Purpose Initiatives to facilitate these practices include the 5 A’s (i.e., Ask, Advise, Assess, Assist, Arrange) and Ask Advise Refer (AAR). Unfortunately, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 22 publications
1
80
1
Order By: Relevance
“…31,32,47,53,58 Students in several studies were more likely to ask and advise about tobacco use than engage in the other 5 As (assess, assist, arrange). 72 In Ask-Advise-Connect, the patient completes a form during the health care visit and the provider submits information directly to the quitline through an electronic or faxed system. 72 In Ask-Advise-Connect, the patient completes a form during the health care visit and the provider submits information directly to the quitline through an electronic or faxed system.…”
Section: Dental Student Practice Of Tobacco Cessationmentioning
confidence: 99%
“…31,32,47,53,58 Students in several studies were more likely to ask and advise about tobacco use than engage in the other 5 As (assess, assist, arrange). 72 In Ask-Advise-Connect, the patient completes a form during the health care visit and the provider submits information directly to the quitline through an electronic or faxed system. 72 In Ask-Advise-Connect, the patient completes a form during the health care visit and the provider submits information directly to the quitline through an electronic or faxed system.…”
Section: Dental Student Practice Of Tobacco Cessationmentioning
confidence: 99%
“…The goal of this initiative is to identify hospitalized tobacco users and those in hospital-affiliated outpatient clinics, assess their readiness to make a quit attempt, and refer them to the Oklahoma Tobacco Helpline. Prior studies [12][13][14] have demonstrated that tobacco-cessation referral programs delivered through hospitals and clinics reach substantial numbers of tobacco users and effectively link them to quitline services. This paper describes the implementation of the OHA hospital-based intervention and quitline referral initiative, Hospitals Helping Patients Quit.…”
Section: Introductionmentioning
confidence: 99%
“…More research needs to be done utilizing electronic health record (EHR) to support implementation of CEASE and to support clinicians' ability follow-up with identified smokers. Other studies have shown that EHR integration can increase referral rates to Quitlines [15][16][17], suggesting that integrating tobacco treatment into EHRs is a high yield area for intervention. In addition, this study did not incorporate patient perspectives on screening and smoking support strategies, more research is needed to incorporate diverse patient perspectives further inform effective smoking cessation support interventions to improve interventions and address health disparities.…”
Section: Resultsmentioning
confidence: 99%